Legality as a principle of organization and activity of executive authorities in the Russian Federation: constitutional and legal analysis - Goncharov, Vitaliy V.; Zalesny, Jacek; Poyarkov, Sergey Yu. (Opción, 2020)
This article is devoted to the constitutional analysis of the most important principle of organization and activity of executive authorities in the Russian Federation - legality. The authors have developed and justified a set of recommendations on strengthening and strengthening the rule of law and order in the activities of executive bodies and the responsibility of their officials.